Knowledge and Health Beliefs Regarding Sickle Cell Disease Among Omanis in a Primary Healthcare Setting : Cross-sectional study - Mohammed H. Al-Azri; Rajaa Al-Belushi; Muna Al-Mamari; Robin Davidson; Anil C. Mathew (Sultan Qaboos University Medical Journal, 2016)
Objectives: Sickle cell disease (SCD) is a global health concern associated with high childhood morbidity and mortality; in Oman, the prevalence of SCD is 0.2%. Public awareness of SCD and the need for premarital screening (PMS) are essential to reduce the incidence of this disease. This study aimed to assess awareness of and beliefs regarding SCD and PMS among Omanis in a primary healthcare setting. Methods: This cross-sectional study took place in five health centres located in Al-Seeb Province, Muscat, Oman, between June and August 2015. A total of 500 Omanis aged ≥18 years old attending the clinics were invited to participate in the study. A previously described questionnaire by Gustafson et al. was used to measure awareness of and beliefs regarding SCD and PMS. Results: A total of 450 Omani adults completed the questionnaire (response rate: 90.0%). The majority (67.8%) were aware that SCD is genetically inherited and 85.1% believed in the value of PMS; however, only 24.4% reported having undergone PMS previously. Few participants were aware that SCD can be very painful (20.2%) and can cause strokes, infections and organ damage (20.0%). More than half (56.7%) reported that the availability of educational material on SCD or PMS in Oman was inadequate. Participants’ education levels were positively associated with accurate SCD knowledge (P <0.05). Conclusion: Despite the free availability of PMS services in local health centres, few Omanis reported having undergone PMS previously. Health promotion and education programmes are therefore needed in Oman in order to increase public awareness of SCD and the value of PMS.